Optimalisasi Pengelolaan Kelas Secara Daring Melalui Media Pembelajaran - Irna Nurul Ainie; Vania sasikirana; Tin Rustini (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2022)
Learning media is a part of the learning component that is used as a tool that can help the learning process, so that learning objectives can be conveyed properly. However, in practice learning media is very rarely applied in classroom management. This study discusses the problem of online learning. Where the implementation of learning is still not optimal, this is because teachers are still not able to optimize the use of learning media and learning management in the implementation of classroom management. The purpose of this study is to find out how important the role of learning media in classroom management is in boldly. This research was conducted through an approach approach. Data was collected by interviewing elementary school teachers in one elementary school in Garut Regency, West Java Province and literature studies. The results of this study conclude that if the learning process is carried out by optimizing the learning media, then the classroom management carried out by the teacher will be better, the learning objectives will be achieved easily and optimally.